Study on Construction Status and Development Suggestions of Intelligent Connected Vehicle Test Area in China - Feng, Qianlong; Kang, Kai; Ding, Qian; Yang, Xianglu; Wu, Shuo; Zhang, Fan (International Journal of Global Economics and Management, 2024)
Intelligent connected vehicle is the key to the competition in the second half of the automotive industry reform As a key link before technical iteration and commercial application, the test, evaluation, and demonstration application of intelligent connected vehicles have been highly valued by the state and local governments This paper focuses on summarizing the construction of the intelligent connected vehicle test area zone in China, analyzing the construction progress and advanced achievements of the main test zone and pilot zone, and then summarizing the advanced achievements, studying and judging the problems existing in the development of the test area zone, and pushing forward target measures and suggestions to help The high quality development of the intelligent connected vehicle industry in China.